Historyk języka w edytorstwie naukowym - Kozaryn, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The paper deals with the way of constructing linguistic commentaries to the Middle Polish texts being published by Prof. Wojciech Ryszard Rzepka together with Wiesław Wydra, Maria Adamczyk or Alojzy Sajkowski. The observations carried out show that semantic explanations— being the main framework of linguistic commentaries made by Prof. Rzepka—become a specific excuse to show and describe grammatical forms, make a classification of language forms on the grounds of their regional, terminological and systemic affinity, highlight the form’s antiquity, and, consequently, to show the development of language throughout history. The use of linguistic terminology in the commentaries, on the one hand, and the citation of linguistic references in explanations which refer to specific issues, on the other hand, show confidence of Prof. Rzepka that the concerned recipients of edited texts have possessed the basic philological knowledge but also the desire and the need to expand it. Presenting the lexical background in a commentary, apart from highlighting the variation of language over time, allows one also to see how an editor works—reaching out to various sources in search of the best interpretative hypothesis, as well as vast knowledge acquired which the author of explanations willingly shares with readers. Accuracy and details of the performed reasoning do not undermine the use of modal denotations—maybe, supposedly, probably—in some explanations. Sharing doubts with recipients is rather an expression of Prof. Rzepka’s incredible modesty, who, himself being a paragon, also sets the bar very high for language historians in the field of scientific editorship who would like to follow in His footsteps.